Sistema de gestión del conocimiento para la seguridad del paciente y análisis de eventos adversos en IPS, profesionales independientes y transporte asistencial (2021)
The health system for patient safety has evolved from the application of manual methods to the description in databases of support tools, however there is still no intelligent management system that facilitates the timely response to patients. Therefore, this research developed a knowledge management system for patient safety in order to solve the main problems in the quality and health care provided by Benefit Plan Administration Entities (eapb, in Spanish), Health Service Provider Institutions (IPS, in Spanish), Special Patient Transport Services, independent professionals, as well as to generate interaction of such information with departmental, district and municipal health entities, the National Health Institute and Technical Agency for the Administration of the High Cost Account. For this purpose, the current situation was characterized through the technological quantitative description method based on a cascade description, promoting the use of digital health technologies, expanding health information systems, and collecting strict surveillance data. In this way, it is expected to facilitate the notification and analysis of risks, adverse events and other mandatory indicators, as well as the reporting to territorial health entities in Colombia, contributing to the implementation and improvement of safe health care practices through the monitoring of safety and quality management indicators.